Melatonin imparts tolerance to combined drought and high-temperature stresses in tomato through osmotic adjustment and ABA accumulation - Mumithrakamatchi, Annadurai K.; Alagarswamy, Senthil; Anitha, Kuppusamy; Djanaguiraman, Maduraimuthu; Kalarani, M. Karuppasami; Swarnapriya, Ramakrishnan; Marimuthu, Subramanian; Vellaikumar, Sampathrajan; Kanagarajan, Selvaraju (Frontiers in Plant Science, 2024)
The effects of combined drought and high temperature (HT) stress during the flowering stage were investigated. The main objective was to assess the effects of foliar spray of melatonin under both individual and combined drought and HT stress at the flowering stage. Drought stress was imposed by withholding irrigation, while HT stress was imposed by exposing the plants to an ambient temperature (AT)+5°C temperature. The drought+HT stress was imposed by exposing the plants to drought first, followed by exposure to AT+5°C temperature. The duration of individual and combined drought or HT stress was ten days. The results showed that drought+HT stress had a significant negative effect compared to individual drought or HT stress alone. However, spraying 100 µM melatonin on the plants challenged with individual or combined drought and HT stress, showed a significant increase in total chlorophyll content [drought: 16%, HT: 14%, and drought+HT: 11%], Fv/Fm [drought: 16%, HT: 15%, and drought+HT: 13%], relative water content [drought: 10%, HT: 2%, and drought+HT: 8%], and proline [drought: 26%, HT: 17%, and drought+HT: 14%] compared to their respective stress control. Additionally, melatonin positively influenced the stomatal and trichome characteristics compared to stress control plants. Also, the osmotic adjustment was found to be significantly increased in the melatonin-sprayed plants, which, in turn, resulted in an increased number of fruits, fruit set percentage, and fruit yield. Moreover, melatonin spray also enhanced the quality of fruits through increased lycopene content, carotenoid content, titratable acidity and ascorbic acid content, compared to the stress control. Overall, this study highlights the usefulness of melatonin in effectively mitigating the negative effects of drought, HT, and drought+HT stress, thus leading to an increased drought and HT stress tolerance in tomato.